2008
DOI: 10.1007/s11270-008-9854-1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Forest Canopy on Total and Methyl Mercury Deposition in the Boreal Forest

Abstract: Atmospheric mercury deposition by wet and dry processes contributes mercury to terrestrial and aquatic systems. Factors influencing the amount of mercury deposited to boreal forests were identified in this study. Throughfall and open canopy precipitation samples were collected in 2005 and 2006 using passive precipitation collectors from pristine sites located across the Superior National Forest in northern Minnesota, USA. Samples were collected approximately every 2 weeks and analyzed for total (THg) and methy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
37
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 21 publications
12
37
0
1
Order By: Relevance
“…This was probably due to dry deposition of MeHg to foliage. The average fractions of THg present as MeHg in precipitation and throughfall were 1% and 1.1%, respectively, which were comparable or lower than values reported for Europe and North America (Porvair and Verta, 2003;Hall et al, 2005;Witt et al, 2009), as well as an upland forest in Mt. Gongga in southwest China (Fu et al, 2010).…”
Section: Deposition Fluxes Of Hg In Precipitation Throughfall and LIsupporting
confidence: 62%
See 1 more Smart Citation
“…This was probably due to dry deposition of MeHg to foliage. The average fractions of THg present as MeHg in precipitation and throughfall were 1% and 1.1%, respectively, which were comparable or lower than values reported for Europe and North America (Porvair and Verta, 2003;Hall et al, 2005;Witt et al, 2009), as well as an upland forest in Mt. Gongga in southwest China (Fu et al, 2010).…”
Section: Deposition Fluxes Of Hg In Precipitation Throughfall and LIsupporting
confidence: 62%
“…Leigong were comparable or lower than those reported in North America and Europe (Schwesig and Matzner, 2000;St. Louis et al, 2001;Hall et al, 2005;Choi et al, 2008;Witt et al, 2009). This is quite different from atmospheric GEM concentrations, which were elevated compared to sites in Europe and North America.…”
Section: Deposition Fluxes Of Hg In Precipitation Throughfall and LImentioning
confidence: 91%
“…Moreover fluxes of T-Hg in forest floor leachates are lower in coniferous stands than in deciduous stand, with a difference in annual T-Hg fluxes estimated at 23% with respect to vegetation composition for lakes in the Adirondak region (Demers et al 2007). Several studies have also shown that open forest areas, grasslands and scrublands are sites of lower Hg deposition leading to reduced [T-Hg] in litterfall as in addition to lower Hg fluxes in soils (Sheehan et al 2006;Poulain et al 2007;Nelson et al 2007;Witt et al 2008). Second, in these studied watersheds, a previous study revealed that coniferous and open areas are mainly found in very low slope and illdrained areas that act as buffer zones for TOM transfer to the lake (Teisserenc 2009).…”
Section: Hg and Tom Sourcesmentioning
confidence: 78%
“…Second, in these studied watersheds, a previous study revealed that coniferous and open areas are mainly found in very low slope and illdrained areas that act as buffer zones for TOM transfer to the lake (Teisserenc 2009). These results are particularly significant as the role of vegetation on Hg uptake and transfer in a watershed is a key parameter to understand Hg cycle in the boreal ecosystem (Grigal 2003;Sheehan et al 2006;Demers et al 2007;Poulain et al 2007;Witt et al 2008).…”
Section: Hg and Tom Sourcesmentioning
confidence: 96%
“…We calculated throughfall Hg deposition from precipitation Hg deposition by adjusting to an enrichment factor K (i.e., the ratio of throughfall/precipitation Hg deposition fluxes). The enrichment factor K varies by tree type [60], which differ in their ability to capture, adsorb, and mobilize Hg forms. For the deciduous forest, we used an enrichment factor of 1.03 (throughfall Hg deposition 12.0 g m yr, and precipitation Hg deposition 11.6 g m yr) found by Choi et al [61] for the deciduous forest in the Adirondacks.…”
Section: Methodsmentioning
confidence: 99%